Arbeitsmigration in Österreich mit Blick auf Vorarlberg/Labor Migration in Austria with references to Vorarlberg - Nele Gfader (Historia.scribere, 2016)
This paper is about labor migration in Austria and Vorarlberg. The paper includes a definition of the essential concepts of migration. In the following chapters the Austrian and Vorarlberg migration history, the government regulated recruitment of Turkish guest-workers and their historical and economic importance will be displayed. The focus of this paper is to show which historical developments have caused recruitment of foreign workers and which positive and negative effects this political move had for Austria and also for the migrants themselves.